PROMOTION AND STORE LISTING CONTENT STRATEGY TO INCREASE CONVERSION RATE OF LICENSED CASUAL MOBILE GAME: STUDY CASE ONET ASLI TAHILALATS - Ardiansyah, Fikry
The development of the game industry in the world is growing very rapidly and creating business potential with exceptional value, including in Indonesia. The Indonesia games market is at top 20 countries by game revenues in the past four years and showed significant growth. There are 83% of game users from the number of internet users in 2018 in Indonesia. Mobile gaming is the largest segment in 2018, claiming more than $313.6 million that consumer spend on mobile games from Indonesia total game revenues combined smartphone and tablet. This shows that Indonesia is the big market and a potential market for game developers. Nowadays, casual gaming on smartphones has become overwhelmingly popular. The reasons is because there’s no hassle, and most people in Indonesia want games that they can pop into and play for a few minutes before closing the app and not going back until they have another spare moment. And then there is low-cost factor and mostly are free to play. Casual games usually have little to no story line so the game is essentially what you make it out to be and anyone can enjoy them. In Indonesia, game developer company are increasingly using the brand awareness and popularity of major intellectual properties (IP) to make their games stand out. By tying their games to popular movies, TV shows or comics characters, they are hoping to drive user installs and revenues. At the same time, IP owners see games as a way to gain additional consumer revenues. Games based on IP have a history of failure and success, making it crucial to understand what makes a licensed game great, and who plays and spends in these games. Onet Asli is one of the casual games that has an IP licenses and make it as a licensed games from Agate. The use of this license is expected to help Agate in acquiring more organic users. Tahilalats as a comic has been known to many people before and has many a loyal readers. As time goes by, the results obtained were not satisfactory enough. The number of visitor to store listings in the play store compared to conversion to download of this game does not produce satisfactory results. The use of Tahilalats has an effect on increasing conversion to traffic, which is traffic to store listings, but not for the conversion rates to download. Through the analysis conducted from internal and external business environment and user analysis using focus group discussion and A/B testing using analysis of variance, it is found out that in order to improve conversion rate, Agate needs to make a strategy with the right flow that starts from retargeting, which changes non-users who already like tahilalats comics and haven't installed the game to become loyal users. Then the promotion strategy with several objectives to increase visits to the store listing page, and in the end optimize the store listing page so that each visit that comes from promotional activities results in a conversion.